Bisphenol A promotes hyperuricemia via activating xanthine oxidase. Issue 2 (4th January 2018) - Ma, Linqiang; Hu, Jinbo; Li, Jiayu; Yang, Yi; Zhang, Linkun; Zou, Lingyun; Gao, Rufei; Peng, Chuan; Wang, Yue; Luo, Ting; Xiang, Xiaojiao; Qing, Hua; et al.
Abstract : The prevalence of hyperuricemia has increased rapidly over the past decades. Bisphenol A (BPA) is an environmental endocrine disruptor. We investigated the effects of BPA on uric acid metabolism and its potential mechanisms. Experiments were performed in different animal models, cell cultures, and humans. In 3 different animal models, BPA exposure increased serum and hepatic uric acid with enhanced activity of xanthine oxidase (XO) in liver, whereas the excretion of uric acid was unchanged. Both in vivo and in vitro, BPA‐induced uric acid production was decreased after treatment with allopurinol, which is a XO inhibitor. XO led to the accumulation of uric acid after xanthine was added, with the enzyme‐catalyzed reaction, which was enhanced by BPA. Altered secondary structures of XO were found by circular dichroism analysis in the conditions of different BPA concentrations. Molecular docking portrayed Asp360 and Lys422 of XO to be the preferred binding sites for BPA. Mutation of both sites significantly blocked the effect of BPA on XO activity. In humans, patients with hyperuricemia exhibited higher levels of serum BPA than subjects without hyperuricemia. These findings demonstrate BPA promotes hyperuricemia by increasing hepatic uric acid synthesis via the activation of XO, probably through direct binding.—Ma, L., Hu, J., Li, J., Yang, Y., Zhang, L., Zou, L., Gao, R., Peng, C., Wang, Y., Luo, T., Xiang, X., Qing, H., Xiao, X., Wu, C., Wang, Z., He, J. C., Li, Q., Yang, S. Bisphenol A promotes hyperuricemia via activating xanthine oxidase. FASEB J. 32, 1007–1016 (2018). www.fasebj.org